Clinical characteristics analysis of pediatric spinal cord injury without radiological abnormality in China: a retrospective study - Renfeng Liu; Qizhi Fan; Jingpeng He; Xin Wu; Wei Tan; Zuyun Yan; Weiguo Wang; Zhiyue Li; You-Wen Deng (BMC, 2024)
Abstract Purpose This study aims to analyze the clinical characteristics of Chinese children with spinal cord injury (SCI) without radiographic abnormality (SCIWORA) and explore their contributing factors and mechanisms of occurrence. Methods A retrospective analysis was conducted on the clinical data of pediatric patients diagnosed with SCIWORA from January 2005 to May 2020. Epidemiological, etiological, mechanistic, therapeutic, and outcome aspects were analyzed. Results A total of 47 patients with SCIWORA were included in this study, comprising 16 males and 31 females. The age range was 4 to 12 years, with an average age of 7.49 ± 2.04 years, and 70% of the patients were below eight. Sports-related injuries constituted 66%, with 70% attributed to dance backbend practice. Thoracic segment injuries accounted for 77%. In the American Spinal Injury Association (ASIA) classification, the combined proportion of A and B grades accounted for 88%. Conservative treatment was chosen by 98% of the patients, with muscle atrophy, spinal scoliosis, hip joint abnormalities, and urinary system infections being the most common complications. Conclusion SCIWORA in Chinese children is more prevalent in those under eight years old, with a higher incidence in females than males. Thoracic spinal cord injuries are predominant, dance backbend as a primary contributing factor, and the social environment of "neijuan" is a critical potential inducing factor. Furthermore, the initial severity of the injury plays a decisive role in determining the prognosis of SCIWORA.